The verbal morphology and phonology of Asante Twi - Mary Paster (LibraryPress@UF, 2010)
This paper presents an analysis of the verbal morphology and associated phonological processes in Asante Twi, a member of the Akan group of languages/dialects spoken in Ghana and Côte d’Ivoire, which belongs to the Nyo subgroup of the Kwa language family (Lewis 2009). There has been considerable interest in Akan in the theoretical literature, largely due to some peculiarities in the tense/aspect system which will be addressed later in this paper. However, the verbal morphology and phonology have been given relatively little attention. In this paper I show that the verbal morphology exhibits a number of interesting properties including tonal marking of tense/aspect categories – the latter having been largely ignored or misrepresented in the previous literature.